Who Undermines the Welfare State?: Austerity-Dogmatism and the U-Turn in Swedish Asylum Policy - Scarpa, Simone (Social Inclusion, 2018)
Within the EU, the so-called "refugee crisis" has been predominantly dealt with as an ill-timed and untenable financial burden. Since the 2007-08 financial crisis, the overarching objective of policy initiatives by EU-governments has been to keep public expenditure firmly under control. Thus, Sweden’s decision to grant permanent residence to all Syrians seeking asylum in 2013 seemed to represent a paradigmatic exception, pointing to the possibility of combining a humanitarian approach in the "long summer of migration" with generous welfare provisions. At the end of 2015, however, Sweden reversed its asylum policy, reducing its intake of refugees to the EU-mandated minimum. The main political parties embraced the mainstream view that an open-door refugee policy is not only detrimental to the welfare state, but could possibly trigger a "system breakdown". In this article, we challenge this widely accepted narrative by arguing that the sustainability of the Swedish welfare state has not been undermined by refugee migration but rather by the Swedish government’s unbending adherence to austerity politics. Austerity politics have weakened the Swedish welfare state’s socially integrative functions and prevented the implementation of a more ambitious growth agenda, harvesting a potentially dynamic interplay of expansionary economic policies and a humanitarian asylum policy.